What Top 25 Most Cited JIBS Articles Can Tell Us About The Firm’s Internationalization Process? - Brambilla, Flávio Régio (Desenvolvimento em Questão, 2014)
This paper aims to a theoretical approach based on the top 25 most cited articles published in the Journal of International Business Studies (JIBS). Based on a list made by the editorial of JIBS, throughout the Web of Science consult, in early 2009 a list was developed based on the citation numbers in other articles, without self citation that was removed from the final sum. The compilation is presented in this paper in an analytical approach, to explore content of that production list. The 25 list is composed by 26 titles, because equal number of citation in 25th. To improve the results, some articles out of the list and JIBS are cited as complementation.